2017
DOI: 10.5937/turizam1702090y
|View full text |Cite
|
Sign up to set email alerts
|

Foreign tourists' risk perceptions about Turkey: An application in Antalya region

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…While a survey of English and German tourists found that international tourists were influenced by health, delinquency, accident, environmental, and natural disaster risk in their decision-making (Carballo et al, 2017). However, another study found that physical risk only influenced German tourists when considering Turkey as a tourism destination (Yağmur & Doğan, 2017). While Wang (2017) found that Chinese tourists were affected by perceived natural and social risk when considering Taiwan as a tourism destination.…”
Section: Perceived Risk and Post-crisis Travel Behaviourmentioning
confidence: 99%
“…While a survey of English and German tourists found that international tourists were influenced by health, delinquency, accident, environmental, and natural disaster risk in their decision-making (Carballo et al, 2017). However, another study found that physical risk only influenced German tourists when considering Turkey as a tourism destination (Yağmur & Doğan, 2017). While Wang (2017) found that Chinese tourists were affected by perceived natural and social risk when considering Taiwan as a tourism destination.…”
Section: Perceived Risk and Post-crisis Travel Behaviourmentioning
confidence: 99%